2011
DOI: 10.1016/j.psychres.2011.03.013
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of adherence to hypoglycemic medications between Type 2 diabetes patients with and without serious mental illness

Abstract: Inadequate self-management of chronic medical conditions like Type 2 diabetes may play a role in the poor health status of individuals with serious mental illnesses. We compared adherence to hypoglycemic medications and blood glucose control between 44 diabetes patients with a serious mental illness and 30 patients without a psychiatric illness. The two groups did not differ in their ability to manage a complex medication regimen as assessed by a performance-based measure of medication management capacity. How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 42 publications
3
42
0
1
Order By: Relevance
“…Another possible explanation is patients' established experience with managing a chronic medical condition (i.e., SMI). Both of these potential explanations are consistent with literature indicating that adherence to diabetes medications in veterans with SMI is better than those without SMI and improves with visit frequency (28,29).…”
Section: Discussionsupporting
confidence: 88%
“…Another possible explanation is patients' established experience with managing a chronic medical condition (i.e., SMI). Both of these potential explanations are consistent with literature indicating that adherence to diabetes medications in veterans with SMI is better than those without SMI and improves with visit frequency (28,29).…”
Section: Discussionsupporting
confidence: 88%
“…Additionally, searching the reference lists of retrieved studies identified 2 further studies which were eligible for inclusion in this review (Dixon et al, 2004;Nelson et al, 2011). Therefore, these 4 articles were added to the 6 studies from our original search (Dolder et al, 2003;Farley et al, 2012;Hansen et al, 2012;Kreyenbuhl et al, 2011;Kreyenbuhl et al, 2010;). In total, 10 articles were included in this review, reporting data from 33,910 psychiatric patients, 94.6% of which had a confirmed diagnosis of schizophrenia / schizoaffective disorder.…”
Section: Search Resultsmentioning
confidence: 99%
“…with at least 80% of days covered by medications) over a 12-month or 24-month timeframe (Desai et al, 2014;Farley et al, 2012;Hansen et al, 2012;Kreyenbuhl et al, 2010;Kreyenbuhl et al, 2011;Nelson et al, 2011;Piette et al, 2007;Simard et al, 2015). In total, 57.6% of patients with schizophrenia were adherent to diabetes medications (N=6, n=33,680; 95% CI=48.5%-66.5%, Q=1243, p<0.01, I 2 =99.6%).…”
Section: Proportion Of Adherent Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Similar findings have been reported from integrated care in both Canada and the US. 11,12 Continuity of primary care is associated with treatment retention and survival benefit. 13 Psychoses are more common among black African or Caribbean groups, 14,15 and the accumulation of cardiovascular risk factors in these groups is associated with additional comorbidities and mortality.…”
Section: Introductionmentioning
confidence: 99%